An investigation into L1 interference in Lao EFL students’ writing and translation for curriculum and teaching improvement - Khamphone Duangpaserth; Yommala Meunviseth; Sonexay Chanboualapha (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
L1 interference in Lao students’ English writing and translation is widely believed to be a source of errors, but it has not been taken into account. As a result, students’ English becomes interlanguage which is considered as an error. This research aimed at investigating the students’ errors in English writing and translation. To collect data, writing and translation tests were administered to 213 (= 30%) EFL university students in the Department of English Language (DEL) in a university in Vientiane Capital, Lao People’s Democratic Republic (Lao PDR). The data were annually analyzed, categorized and counted up participants making errors in percentage. It took approximately six months to finish analyzing errors in 213 English paragraphs and 213 translation-test papers. Both grammatical and lexical errors in sentence level were found due to direct translation word for word from Lao into English. It was also found the percentage of participants making errors in writing and translation was not much different. The results could be used in the curriculum and teaching improvement.